2016
DOI: 10.3349/ymj.2016.57.5.1063
|View full text |Cite
|
Sign up to set email alerts
|

Dyspnea as a Prognostic Factor in Patients with Non-Small Cell Lung Cancer

Abstract: PurposeTo investigate associations between dyspnea and clinical outcomes in patients with non-small cell lung cancer (NSCLC).Materials and MethodsFrom 2001 to 2014, we retrospectively reviewed the prospective lung cancer database of St. Paul's Hospital at the Catholic University of Korea. We enrolled patients with NSCLC and evaluated symptoms of dyspnea using modified Medical Research Council (mMRC) scores. Also, we estimated pulmonary functions and analyzed survival data.ResultsIn total, 457 NSCLC patients we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 21 publications
(23 reference statements)
0
18
0
2
Order By: Relevance
“…Respiratory symptoms such as cough, sputum, and dyspnea were more frequent in patients with NSCLC and COPD than in those without, which supports the hypothesis and is consistent with the results of previous studies [ 25 ]. Declines in lung function and the severity of symptoms in patients with lung cancer are known to have significant effects on quality of life [ 26 ], and in particular, patients who suffer from dyspnea are known to be at higher risk of death and poor prognosis than those without dyspnea [ 6 , 8 ]. Therefore, in this study, the quality of life in patients with advanced NSCLC was analyzed using the EORTC QLQ-C30 scale.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Respiratory symptoms such as cough, sputum, and dyspnea were more frequent in patients with NSCLC and COPD than in those without, which supports the hypothesis and is consistent with the results of previous studies [ 25 ]. Declines in lung function and the severity of symptoms in patients with lung cancer are known to have significant effects on quality of life [ 26 ], and in particular, patients who suffer from dyspnea are known to be at higher risk of death and poor prognosis than those without dyspnea [ 6 , 8 ]. Therefore, in this study, the quality of life in patients with advanced NSCLC was analyzed using the EORTC QLQ-C30 scale.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, various symptoms, including dyspnea and quality of life, affect the prognosis of patients with lung cancer. In particular, respiratory symptoms and changes in pulmonary function, which serve as diagnostic criteria for COPD, have a very negative impact on the prognosis of patients with lung cancer [ 6 8 ]. Many studies have reported the prevalence of COPD and its effects and prognosis in patients with lung cancer, but few have considered quality of life and survival of patients with lung cancer according to severity of airway obstruction.…”
Section: Introductionmentioning
confidence: 99%
“…Breathlessness is a common symptom in patients with cancer ( 1 , 2 ) and is the commonest amongst patients with lung cancer ( 3 ) and among patients in need of palliative care or advanced cancer ( 4 ). As classified by the American Thoracic Society in 1999 (5, p. 322), breathlessness is a subjective experience of difficulty in breathing that consists of qualitative distinctive sensations that differ in intensity.…”
Section: Introductionmentioning
confidence: 99%
“…Ex-smoker was defined as the patient who quitted smoking at least one month before the diagnosis of lung cancer. The patient who had smoked fewer than 100 cigarettes in their lifetime or had never smoked as never smoker [7]. Lung function test was performed according to the American Thoracic Society/European Respiratory Society standardization guidelines.…”
Section: Data Sourcementioning
confidence: 99%